Sex estimation from the scapula in a contemporary Thai population: Applications for forensic anthropology - Tanya R. Peckmann (2018)
© 2017 The Chartered Society of Forensic Sciences The impact of climate change is estimated to be particularly severe in Thailand. Overall, the country faces an increase in surface temperatures, severe storms and floods, and a possible increase in the number of mass disasters in the region. It is extremely important that forensic scientists have access to sex estimation methods developed for use on a Thai population. The goal of this project is to evaluate the accuracy of sex estimation discriminant functions, created using contemporary Mexican and Greek populations, when applied to a contemporary Thai sample. The length of the glenoid cavity (LGC) and breadth of the glenoid cavity (BGC) were measured. The sample included 191 individuals (95 males and 96 females) with age ranges from 19 to 96 years old. Overall, when the Mexican and Greek discriminant functions were applied to the Thai sample they showed higher accuracy rates for sexing female scapulae (83% to 99%) than for sexing male scapulae (53% to 92%). Size comparisons were made to Chilean, Mexican, Guatemalan, White American, and Greek populations. Overall, in males and females of the Thai sample, the scapulae were smaller than in the Chilean, Mexican, White American, and Greek populations. However, the male and female Thai scapulae were larger than in the Guatemalan sample. Population-specific discriminant functions were created for the Thai population with an overall sex classification accuracy rate of 83% to 88%.